Oxygenation failure after cardiac surgery: early re-intubation versus treatment by nasal continuous positive airway pressure (NCPAP) or non-invasive positive pressure ventilation (NPPV) - Muhammed Kurt; Udo Boeken; Jens Litmathe; Peter Feindt; Emmeran Gams (Monaldi Archives for Chest Disease, 2016)
Background: Due to an increasing incidence of respiratory failure after cardiac surgery we wanted to study whether nasal continuous positive airway pressure (NCPAP) may improve pulmonary oxygen transfer and may avoid reintubation after coronary operations. Additionally, we compared this protocol to non-invasive positive pressure ventilation (NPPV). Methods: For a period of 2 years we analyzed all patients that were extubated within 12 hours after coronary surgery, and in whom oxygen transfer (PaO2/FIO2) deteriorated without hypercapnia so that all these patients met predefined criteria for reintubation: group A=immediate reintubation (n=88), group B=NCPAP-treatment (n=173), group C=NPPV(n=18). Results: 25,4% of group B- and 22,2% of group C-patients were also intubated after a period of NCPAP or NPPV. All other patients of groups B and C could be weaned from these devices (B = 34.3 ± 5.9 hours; C = 26.4 ± 4.4 h; p<0.05) and were well oxygenated by face mask at ambient pressure (Ratio PaO2/FIO2: B, 138 ± 13; C, 140 ± 13). In group A we found a higher mortality (7.95%) compared to group B (4.04%) and group C (5.55%). NCPAP-patients suffered more frequently from an impaired sternal wound healing (A = 4.5%, B = 8.6%; p<0.05). Conclusions: We conclude that reintubation after cardiac operations should be avoided since NCPAP and NPPV are safe and effective to improve arterial oxygenation in most patients with non hypercapnic respiratory failure.